1981
DOI: 10.1159/000117853
|View full text |Cite
|
Sign up to set email alerts
|

Urinary MHPG, Stress Response, Personality Factors and Somatosensory Evoked Potentials in Normal Subjects and Patients with Major Affective Disorders

Abstract: Stressful procedures are reported to increase urinary MHPG in both noraml and depressed patients. Bipolar depressed patients are alos shown to be especially pain tolerant in comparison to normals. In the present study, 12 depressed patiens (6 bipolar and 6 unipolar patients) and 10 normal volunteers had average evokded potentials recorded for visual and painful electrical stumuli. MHPG urinary excretion was measured during this session and during an unstimulated resting session on the home ward. Male normal vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…The subjects were 43 normals, screened for psychiatric disorders, although ac tual numbers varied for different comparisons because of missing data on some subjects. The results from the pre vious study [Buchsbaum et al, 1981] were not replicated in this study. Instead, both CSF NE and plasma dopa mine-beta-hydroxylase (DBH) were negatively correlated with general sensation seeking.…”
Section: Monoaminescontrasting
confidence: 66%
See 2 more Smart Citations
“…The subjects were 43 normals, screened for psychiatric disorders, although ac tual numbers varied for different comparisons because of missing data on some subjects. The results from the pre vious study [Buchsbaum et al, 1981] were not replicated in this study. Instead, both CSF NE and plasma dopa mine-beta-hydroxylase (DBH) were negatively correlated with general sensation seeking.…”
Section: Monoaminescontrasting
confidence: 66%
“…The first data on sensation seeking and the mono amines came from a study by Buchsbaum et al [1981]. Urinary MHPG was measured in 12 depressed patients and 10 normal volunteers under resting and stressful con ditions.…”
Section: Monoaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical stress, such as electrical stimulation applied to the forearm, has been found to increase urinary MHPG (10). According to Drebing et al (11), the saliva level of MHPG correlates significantly with the plasma level of MHPG, and it can be a useful and noninvasive tool for detecting changes in central norepinephrine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Free-3-mehoxy-4-hydroxyphenylglycol (free-MHPG) (Okamura, 2010;Buchsbaum, 1981) and testosterone was reported to show transient increase by short-term laboratory stressors, while the number of studies assessing these substances are very small and frequently showed inconsistent results (e.g. Schoofs, 2011).…”
Section: Other Salivary Possible Biomarkersmentioning
confidence: 99%